Application of single and cooperative different delivery systems for the treatment of intervertebral disc degeneration - Liu, Zongtai; Fu, Changfeng (Frontiers in Bioengineering and Biotechnology, 2022)
Intervertebral disc (IVD) degeneration (IDD) is the most universal pathogenesis of low back pain (LBP), a prevalent and costly medical problem across the world. Persistent LBP can seriously affect a patient’s quality of life and even lead to disability. Furthermore, the corresponding medical expenses create a serious economic burden to both individuals and society. IDD is commonly thought to be related to age, injury, obesity, genetic susceptibility and other risk factors. Nonetheless, its specific pathological process has not been completely elucidated; the current mainstream view considers that it this condition arises from the interaction of multiple mechanisms. With the development of medical concepts and technology, clinicians and scientists tend to intervene in the early or middle stages of IDD to avoid further aggravation. However, with the aid of modern delivery systems, it is now possible to intervene in the process of IVD at the cellular and molecular levels. This review aims to provide an overview of the main mechanisms associated with IDD and the delivery systems that can help us to improve the efficacy of IDD treatment.